2001
DOI: 10.1093/emboj/20.1.91
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of signaling by STAT1 depends on SH2 and C-terminal domains that regulate Ser727 phosphorylation, differentially affecting specific target gene expression

Abstract: Complete activation of signal transducer and activator of transcription 1 (STAT1) requires phosphorylation at both Y701 and a conserved PMS 727 P sequence. S727 phosphorylation of STAT1 in interferon-g (IFN-g)-treated mouse ®broblasts occurred without a need for p38 mitogen-activated protein kinase (MAPK), extracellular signal-regulated kinases 1 and 2 or c-Jun kinases, and required both an intact SH2 domain and phosphorylation of Y701. In contrast, UV irradiation-induced STAT1 phosphorylation on S727 required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
163
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(173 citation statements)
references
References 70 publications
10
163
0
Order By: Relevance
“…In this context, S727-phosphorylated STAT 1 provided apoptotic resistance for Wilms tumour cells (Timofeeva et al, 2006). Although phosphorylation at Y701 was shown to be sufficient for transactivatory capacity of STAT 1 molecule (Shuai et al, 1993), S727 phosphorylation seems to be an important modulator of target specificity in haemopoetic cells (Kovarik et al, 2001). Perhaps high levels of STAT 1 phosphorylation at S727 might activate specific genes involved in IFN resistance.…”
Section: Relation Between Socss Induction and Stat 1 Phosphorylationmentioning
confidence: 99%
“…In this context, S727-phosphorylated STAT 1 provided apoptotic resistance for Wilms tumour cells (Timofeeva et al, 2006). Although phosphorylation at Y701 was shown to be sufficient for transactivatory capacity of STAT 1 molecule (Shuai et al, 1993), S727 phosphorylation seems to be an important modulator of target specificity in haemopoetic cells (Kovarik et al, 2001). Perhaps high levels of STAT 1 phosphorylation at S727 might activate specific genes involved in IFN resistance.…”
Section: Relation Between Socss Induction and Stat 1 Phosphorylationmentioning
confidence: 99%
“…Previous findings indicated that S727 phosphorylated STAT1 acts as an integrator of signals from multiple pathways, resulting in chromatin remodeling and gene activation (Zhang et al, 1998;Ouchi et al, 2000;Kovarik et al, 2001). Therefore, it is conceivable that serine-phosphorylated STAT1 functions as a transcriptional co-activator interacting with other DNA-bound proteins, and its role in cellular processes can be different depending on other proteins expressed and/or activated under the same conditions in cells.…”
Section: Stat1 Is a Prosurvival Factor In Wilms' Tumormentioning
confidence: 99%
“…These studies support the notion that pStat1(ser727) is less critical for IRF-1 expression by stimulation of IFN-γ. However, other studies have reported that IRF-1 expression requires pSTAT1(ser727) (Kovarik et al, 2001;Ramsauer et al, 2002;Varinou et al, 2003). Although the sources of discrepancy between two types of results are not clear at the moment, in all studies, IRF-1 expression was induced by IFN-γ in the absence of serine phosphorylation of Stat1, albeit at a low level.…”
Section: Discussionmentioning
confidence: 76%